Love is a Decision. - Smalley, Gary (Pockets Books, 1993)
Discover a simple yet profound plan for a marriage of depth, warmth, and excitement! Guide your marriage for a lifetime by learning how to make your spouse feel truly honored, keep courtship alive, rebuild trust, and become best friends with your family.Love is more than a feeling. It is a choice. And while that sounds less than romantic, nobody gets married and ever plans on getting a divorce--but every marriage is headed for both happy and hard times. According to family counselor and bestselling author Gary Smalley, good marriages are no accident. And deciding to love--in the practical ways outlined here--can result in relationships that are tougher than those tough times.Using stories from couples he has counseled, spiritual lessons, and emotional word pictures, Smalley teaches biblical principles and practical techniques for building, re-building, and nurturing relationships.This classic guide, perfect for gifting, is ideal for newly engaged couples, newlyweds, and veteran married couples alike. You will learn how to: Learn the art of meaningful conversationEnergize your mate in 60 secondsFind the surprising key to satisfying sexDiscover the surprising secret of a close-knit familyTap into the unfailing power source behind a great marriageIn this timeless bestseller, Smalley and Trent explain how to take advantage of the unique strengths of women and men to forge stronger marriages that will withstand the greatest tests.